Concepts in Physical Chemistry - Atkins, Peter (London : Royal Society of Chemistry, 2024)
Completely revised and updated for a second edition, this reference guide is an essential summary of the key concepts in physical chemistry that are likely to be encountered by undergraduate chemistry students. This book also serves as a useful reference for all who encounter physical chemical concepts in their professional activities or research. Written by a renowned textbook author and educator, this new edition of Concepts in Physical Chemistry is a convenient, easy-to-use, and authoritative reference; the chemical terms, ideas, and equations most frequently encountered in classroom or laboratory are clearly defined and explained.
Keywords: Physical chemistry; Chemical kinetics; Electrochemistry